Preoperative Predictors of Better Long-term Functional Ability and Decreased Pain Following LSS Surgery: A Prospective Observational Study with a 10-year Follow-up Period. Issue 11 (1st June 2020) - Tuomainen, Iina; Pesonen, Janne; Rade, Marinko; Pakarinen, Maarit; Leinonen, Ville; Kröger, Heikki; Airaksinen, Olavi; Aalto, Timo
Abstract : Study Design: A prospective observational 10-year follow-up study. Objective: This study aimed to examine preoperative predictors for better surgical outcomes in patients with lumbar spinal stenosis (LSS) 10 years after surgery. Summary of Background Data: LSS is a leading cause of low back surgery in patients older than 65 years. Limited data are available for predictors of long-term surgical outcomes in patients with LSS. Methods: At the baseline, 102 patients with LSS underwent decompressive surgery, and 72 of the original study sample participated in a 10-year follow-up study. Study patients filled out a questionnaire preoperatively, and follow-up data were collected at 3 months, 6 months, 1 year, 2 years, 5 years, and 10 years postoperatively. Surgical outcomes were evaluated in terms of disability with the Oswestry Disability Index (ODI) and pain with the visual analog scale (VAS). Predictors in the models were nonsmoking status, absence of previous lumbar surgery, self-rated health, regular use of painkillers for symptom alleviation, and BMI. Statistical analyses included longitudinal associations, subgroup analyses, and cross-sectional analyses. Results: Using multivariate analysis, statistically significant predictors for lower ODI and VAS scores at 10 years were nonsmoking status, absence of previous lumbar surgery, better self-rated health, and regular use of painkillers for <12 months. Patients who smoked preoperatively or had previous lumbar surgery experienced more pain and disability at the 10-year follow-up. Conclusion: These study results can enhance informed decision-making processes for patients considering surgical treatment for LSS by showing preoperative predictors for surgical outcomes up to 10 years after surgery. Smokers and patients with previous lumbar surgery showed a decline in surgical benefits after 5 years. Level of Evidence: 3 Abstract : In this study, preoperative predictors for better functional ability and less pain 10 years after surgery were nonsmoking status, absence of previous lumbar surgery, better self-rated health, and control of symptoms by the regular use of painkillers for <12 months preoperatively. Smokers and patients with previous lumbar surgery showed a decline in surgical benefits after 5 years.